2016
DOI: 10.1002/ppap.201600103
|View full text |Cite
|
Sign up to set email alerts
|

Understanding CO2 decomposition in microwave plasma by means of optical diagnostics

Abstract: The growing interest to plasma‐based greenhouse gas decomposition requires the knowledge of the different kinetic mechanisms inherent in CO2 discharges and post‐discharges. This automatically involves extensive plasma diagnostics research work. Among different types of plasma diagnostics, the ones based on optical spectroscopy are of particular relevance due to their non‐intrusiveness. The recent progress in optical diagnostics of plasma‐assisted CO2 decomposition process is discussed in this work. A microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…Note that the gas temperature has been determined in this work based on the time-average spectral data and the time-resolved measurements may be necessary for a full clarification of the temperature evolution. The additional experiments [49] indicate that the vibrational temperature of the N 2 (X) ground state molecules in the active zone decays rapidly under the increase of the pulse repetition frequency, following the trends obtained for CO density (Figure 7(a))a n dC O 2 conversion (Figure 8(a)). Rather fast nonresonant V-V' energy exchange taking place between N 2 and CO 2 (see Ref.…”
Section: Green Chemical Processing and Synthesissupporting
confidence: 66%
See 1 more Smart Citation
“…Note that the gas temperature has been determined in this work based on the time-average spectral data and the time-resolved measurements may be necessary for a full clarification of the temperature evolution. The additional experiments [49] indicate that the vibrational temperature of the N 2 (X) ground state molecules in the active zone decays rapidly under the increase of the pulse repetition frequency, following the trends obtained for CO density (Figure 7(a))a n dC O 2 conversion (Figure 8(a)). Rather fast nonresonant V-V' energy exchange taking place between N 2 and CO 2 (see Ref.…”
Section: Green Chemical Processing and Synthesissupporting
confidence: 66%
“…CO þ O, see Ref. [29]) in this frequency range, as suggested by Silva et al [49], (iii) decomposition of CO molecules in the active zone when residence time is too long. The third argument, however, is supposed to play a minor role, due to the synchronous changes of both CO and O 2 densities observed in the postdischarge detected by GC, as shown in Figure 7(b).…”
Section: Green Chemical Processing and Synthesismentioning
confidence: 55%
“…In the past decade, many papers, both experimental (e.g., Silva et al, 2014Silva et al, , 2017Klarenaar et al, 2017Klarenaar et al, , 2018Klarenaar et al, , 2019Stewig et al, 2020;Terraz et al, 2020;van den Bekerom et al, 2020) and computational (e.g., Bogaerts, 2014, 2015;Pietanza et al, 2015Pietanza et al, , 2017aPietanza et al, ,b, 2018aPietanza et al, ,b, 2020Bogaerts, 2016, 2018;Capitelli et al, 2017, Heijkers andGrofulović et al, 2018;Silva et al, 2018;Bogaerts, 2018, 2019;Kotov and Koelman, 2019;Terraz et al, 2020), focused on the role of the vibrational kinetics in plasmas, but mainly at low pressure conditions (few mbar up to a few hundred mbar). Most of these studies revealed the importance of the vibrational kinetics at specific conditions (low gas temperature, low pressure) and their contribution to a high energy efficiency.…”
Section: Different Dissociation Mechanisms In Different Plasma Typesmentioning
confidence: 99%
“…Since H 2 , O 2 and H 2 O are also used as co-reagents in the plasma valorisation of CH 4 and CO 2 that some of the elementary reactions for the excitation of these molecules are also presented in the More details on plasma excitation mechanisms of the above mentioned molecules can be found elsewhere. 72,73 It can be seen from the Table 2 that CH 4 gets mostly activated by dissociation, where one or more hydrogen atoms get removed. [74][75][76][77] Higher electron energies are required for the removal of more than one hydrogen, so the extent to which each of these processes will take place is heavily dependent on electron energy distribution in a given system.…”
Section: Activation Of Ch 4 and Co 2 In Plasmamentioning
confidence: 99%